2013
DOI: 10.3310/hsdr01140
|View full text |Cite
|
Sign up to set email alerts
|

Towards equitable commissioning for our multiethnic society: a mixed-methods qualitative investigation of evidence utilisation by strategic commissioners and public health managers

Abstract: BackgroundThe health-care commissioning cycle is an increasingly powerful determinant of the health services on offer and the care that patients receive. This study focuses on the mobilisation and use of evidence relating to ethnic diversity and inequality.ObjectiveTo describe the patterns and determinants of evidence use relating to ethnic diversity and inequality by managers within commissioning work and to identify promising routes for improvement.MethodsIn-depth semistructured interviews with 19 national k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Previous studies have identified challenges in developing policies, including limited time and local skills/expertise to systematically identify and appraise evidence. 11 , 23 , 24 Others have suggested that the evidence-culture within commissioning organisations differs to that of medicine, in that the source of evidence (e.g. local relevance) and mode of communication (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified challenges in developing policies, including limited time and local skills/expertise to systematically identify and appraise evidence. 11 , 23 , 24 Others have suggested that the evidence-culture within commissioning organisations differs to that of medicine, in that the source of evidence (e.g. local relevance) and mode of communication (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is commissioning guidance for diabetes services and integrated care which by default covers care for chronic conditions and older people and points to earlier onset, need for services to consider ethnicity [106], but it seems that there has been limited organisational engagement, it has been low priority, and there are limited skills [107]. …”
Section: Discussionmentioning
confidence: 99%
“…8 Considerable literature documents migrant and other ethnic minority experiences with the National Health Service (NHS) before and during austerity, showing many inequities as systemic and longstanding. [9][10][11][12][13][14][15][16][17][18] While austerity measures are not responsible for inequities in service access and quality, combined with rapid recent demographic changes, patterns of social exclusion, and increasingly restrictive immigration policies, austerity leaves some migrants increasingly vulnerable to inequitable health services provision. 7,[19][20][21] The British NHS, established in 1948, is a publicly-funded healthcare system providing universal coverage for users.…”
Section: Introductionmentioning
confidence: 99%